(untitled) - Võ, Thị Cẩm Xuyên (Cần Thơ, 2013)
The present study aims at investigating primary school english teacher's beliefs about teaching L-S skills to YLs and examining the practices of teacher english L-S skills to YLs in the primary school context in other to find out whether their practices are consistent with their beliefs and the reasons for the inconsistency if there are any
Keywords: Tiếng Anh,English; Dạy và học,Study and teaching